Uvodnik / Editorial - Knez, Rajko (LeXonomica, 2021)
The editorial, for which the editor asked me this time, I dedicate much too quickly deceased prof. dr. Mirko Ilešič, who at the Faculty of Law of the University of Maribor worked in the field of commercial law. The reason is this editorial intended for him, there are two. The professor began with an economic analysis of law deal before us all and on September 10 this year it has been ten years since his chosen words, happy comparisons and clear explanations, as well as humorous ones comments, I can no longer hear. An opus of his works, and above all theirs content and the way he approached the writing of scientific ...